LEVERAGING PROJECT UNCERTAINITY: A PRACTICAL APPROACH TO THE CONTRIBUTION OF DESIGN THINKING IN COMPLEX PROJECTS - Morgan , Asena; Nyonje , Prof. Raphael (IJRDO - Journal of Business Management, 2022)
Available literature points out that the complexities of projects have often led to project failure. Insufficient project management standards have led to project uncertainties. The management of project uncertainty lies with the project manager. There is little evidence on empirical literature that is focused on project management and their uncertainty. This paper investigates the practices used by project managers to address project uncertainty and to critically analyze the success of these methods in complex projects by use of design thinking approach in the implementation of projects. The findings of address challenges and concerns facing project managers in managing projects in uncertain environments. This paper will give guide on project design, management and uncertainty .It will further contribute to the theory on uncertainty on project management.